Progressive damage in Sn-4Ag-0.5Cu solder joints during flexural fatigue of a BGA package - Shaffiar, Norhashimah; Loh, W.K.; Kamsah, N. (2010)
This study examines evolution characteristics of inelastic strains and materials damage in Sn-4Ag-0.5Cu (SAC405) solder joints of a BGA package under cyclic mechanical stressing. For this purpose, a finite element model of the assembly under four-point bend test set-up is employed. Strain rate-dependent response of the solder is represented by Anand model. Progressive damage in the solder joint is described using continuum damage model. Results show that the critical solder joint is the one located at the corner of the BGA package. In this critical solder joint, both high stress and inelastic strain are localized in a small edge region at the solder/IMC interface at the board side of the assembly. The different inelastic strain rates experienced by the critical solder joint during fatigue cycles correspond to the distinct damage initiation stage, crack propagation stage and the final fast fracture of the solder joint. Damage initiation life covers nearly half of the total fatigue lives of the critical solder.